CULTURE SHOCK PADA MAHASISWA DI PONTIANAK - Julia wati; Selegam Selegam (The Institute for Research and Community Service (LP2M) of Pontianak State Institute of Islamic Studies (IAIN Pontianak), 2023)
Students from different regions have different cultures. Students often experience culture shock in a new environment. The purpose of this study was to describe the form and background of the occurrence of culture shock in overseas students in Pontianak, as well as how they passed the culture shock. This study uses a descriptive qualitative approach. Source data is obtained through words and actions, written sources as well as photographs. Data collection techniques used in this study are interviews, observation and documentation. Subjects in this study were students from outside the City Of Pontianak. The results showed that overseas students experienced culture shock on food, language, social, academic lectures, and the community environment. These five aspects arise because they are generally different from their previous daily lives. Students claim they can overcome culture shock by trying to learn and adapt and understand the culture of others around them.